Access of the patient to the cancer network under the "Sixty-Day Law": Integrative Review - Mariela Santos Lombardo; Regina Célia Popim (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze Brazilian scientific production on patient access to the oncology network under the "Sixty-Day Law". Methods: integrative review of the literature in the databases Lilacs, PubMed and Scielo. The descriptors used were: neoplasms, health services accessibility, early detection of cancer. Articles published from 2015 to March 2019 were included. Results: 17 articles were analyzed and four themes emerged: inequality in access; qualification of Primary Care professionals; time as a determinant factor; information system as limiting factor. Conclusions: the access to the oncology network is unequal and there are several barriers faced by the users. A continuing education of health professionals is necessary to implement preventive strategies. Treatment initiation is late, showing non-compliance with the law. The health care network is highly fragmented, there is lack of coordination between the services and, consequently, there is a lack of patient follow-up.